2019
DOI: 10.17691/stm2019.11.1.03
|View full text |Cite
|
Sign up to set email alerts
|

Modern Technologies in Studying the Mechanisms, Diagnostics, and Treatment of Autism Spectrum Disorders (Review)

Abstract: Autism spectrum disorders (ASD) are among the most common and intractable neurological diseases characterized by high heterogeneity and requiring a person-oriented approach to diagnostics and treatment. The purpose of this review is to summarize the literature data of the last 5 years on the contribution of modern technologies to the knowledge of mechanisms, diagnostics, and treatment of ASD. Particular attention is paid to the possibilities of non-drug treatment of ASD with the help of neurointerface technolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…Audio-visual stimulation (AVS) has recently attracted increased attention due to a number of advantages: mobility, ease of implementation, fast and complex effects, capability to improve human health and functional state [ 1 – 6 ]. Recent studies have demonstrated the possibility of using AVS to improve sports training regimes [ 7 9 ] and to confirm the differential diagnosis in chronic disorder of consciousness [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Audio-visual stimulation (AVS) has recently attracted increased attention due to a number of advantages: mobility, ease of implementation, fast and complex effects, capability to improve human health and functional state [ 1 – 6 ]. Recent studies have demonstrated the possibility of using AVS to improve sports training regimes [ 7 9 ] and to confirm the differential diagnosis in chronic disorder of consciousness [ 10 ].…”
Section: Introductionmentioning
confidence: 99%